2021
DOI: 10.1111/ijcp.14241
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thiol/disulphide homeostasis changes in patients with relapsing‐remitting multiple sclerosis

Abstract: Background: Multiple sclerosis (MS) is a neuroinflammatory disease and inflammation and oxidative stress play important roles in its pathology. Thiol/disulphide homeostasis (TDH) is a special oxidative stress biomarker that has been found to be affected in several disorders including MS. There is no study demonstrating the effects of attack status of the relapsing-remitting multiple sclerosis (RRMS) patients on TDH levels. Our aim was to determine TDH levels in three different periods of RRMS patients and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…TDH has previously been studied in MS (Arslan et al, 2021;Calabrese et al, 2003;Ozben et al, 2021;Vural et al, 2019) Notes: Regression models were determined according to their partial least square regression results. Native Thiol, Total Thiol, Native Thiol/Total Thiol parameters were analyzed with smoking status in the models for naïve patients with RRMS, whereas Native Thiol, Total Thiol, Albumin parameters were analyzed with 25(OH)-D 3 and HDL-cholesterol levels in the models for RRMS patients with fingolimod therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TDH has previously been studied in MS (Arslan et al, 2021;Calabrese et al, 2003;Ozben et al, 2021;Vural et al, 2019) Notes: Regression models were determined according to their partial least square regression results. Native Thiol, Total Thiol, Native Thiol/Total Thiol parameters were analyzed with smoking status in the models for naïve patients with RRMS, whereas Native Thiol, Total Thiol, Albumin parameters were analyzed with 25(OH)-D 3 and HDL-cholesterol levels in the models for RRMS patients with fingolimod therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TDH has previously been studied in MS (Arslan et al, 2021; Calabrese et al, 2003; Ozben et al, 2021; Vural et al, 2019). Ozben et al have demonstrated that TDH has shifted toward the oxidized disulfide form in patients with RRMS (Ozben et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations